The Impact of Urbanization on the Flow of Traffic in Faisalabad City Pakistan - Hissan, Riaz ul; Waseem , Liaqat Ali; Khurshid, Madiha; Maqbool, Muhammad Shahid (Pakistan Journal of Humanities and Social Sciences, 2023)
It is estimated that 50% of the world's population is living on only 2% of land area. Population scientists also believe that the urban population will increase from 80% to 90% by 2030 which is why urban growth is a significant problem in the developing world. Rapid urbanization has created many problems like haphazard development, disturbance in the ecological system, shortage of shelter and food polluted environment, lack of basic facilities, and traffic congestion. Besides traffic jams, traffic flow is also the major reason for different types of pollution like noise pollution and air pollution, which is a cause of health problems. Pakistan being a developing country experiences the same problems because of rapid urbanization. Faisalabad is the third largest city (according to the rank-size rule) and is famous for the agro cottage and textile industry. It covered the 313.21km2 area. Traffic congestion is a significant problem in Pakistan’s cities because of their unplanned infrastructure and explosive population growth. Faisalabad is the first planned city of the subcontinent. With time, Faisalabad’s infrastructure faced many changes due to uncontrolled urbanization. Road transport increased by 3% yearly due to the usage of personal automobiles. In the usage of personal vehicles, the share of motorcycles is 89 % while the share of cars is 50 %. Rapid urbanization is a severe threat to the city environment. Traffic congestion has become the problem of the day. This menace increased over time due to the slow development of roads and insufficient infrastructure as compared to rapid urbanization.